Fatores que influenciaram a escolha entre estudo e trabalho para os jovens brasileiros no período de 2019 e 2023 - Oliveira, Junior Vieira de (2025)
Between the years 2019 and 2023, we experienced a period, marked by an entire generation, known as the Covid-19 Pandemic years. This period had a significant impact on all aspects of personal and social life for the citizens inhabiting the planet during this time frame. Among its consequences, the impacts on the economy, especially in the labor market, stand out. During this period, Brazil went through a turbulent time marked by successive reforms in its economic plan and early signs of policies excluding minorities. When faced with the Health Crisis in 2020, some patterns of marginalization and social differentiation were intensified, particularly in the youth labor market, which was already out of step with the others. This research aims to analyze the socioeconomic portrait of young people aged 18 to 29 who are not heads of households in the year immediately before the Covid-19 pandemic and after its end (2019-2023). It also aims to understand their perceptions regarding the choice between working and studying, and their possible combinations, as well as considering the role of their income when placed in the labor market. To achieve this purpose, techniques of descriptive statistical analysis were applied, such as graphical analysis and cross-mean analysis, in addition to the equalization of Logit Multinomial using data from the Continuous National Household Sample Survey (PNADC) – 2019/2023. In the Logit Multinomial model, the dependent variable consisted of different combinations between work and study, the NEM-NEM combination (neither studying nor working) as the reference category, the logic established through the model indicated that variables related to location, region, and the youth's race are significant factors contributing to whether they adopt the NEM-NEM behavior. Additionally, changes in the family structure of the household where the youth resided as dependents between the initial period of 2019 and the end of 2023 are highlighted. Therefore, this research aims to encourage future studies in identifying other variables that could contribute to developing an effective framework for creating public policies to combat the NEM-NEM tendency among young people in Brazil.